Experimental study of the parameter effects on the flow and noise characteristics for a contra-rotating axial fan - Zhao, Yanjie; Xu, Chen; Zheng, Zhiwei; Hu, Xiaowen; Mao, Yijun (Frontiers in Physics, 2023)
In the present paper, experiments for a contra-rotating axial fan have been conducted to investigate the influences of the fan parameters including axial distance, blade number, blade pattern and blade thickness on the performance and noise characteristics under variable rotational speed regulation. The results show the characteristic curves of the shaft power and the sound pressure level (SPL) are nearly identical, which indicates the axial distance and blade number are not sensible factors for the contra-rotating axial fan under variable rotational speed regulation. The blade profiles of the fan have an impact on the characteristic curves of the SPL and the shaft power curves of the fan decrease evidently with increase of the blade thickness, while the shaft power curves are very close with different blade patterns. In general, the blade profiles are sensible factors for the contra-rotating axial fan under variable rotational speed regulation. Meanwhile, through the SPL spectrum analysis of the contra-rotating axial fan with different blade profile, it can be concluded that the blade profile of the rotors has an obvious impact on the broadband noise characteristics under moderate and high frequency range. Moreover, the spectrum density of the velocity obtained from the experiment is compared with the classic turbulence models.